METODE DAKWAH QISM AMN UNTUK MENINGKATKAN KEDISIPLINAN IBADAH MAHASISWA SEKOLAH TINGGI ILMU BAHASA ARAB AR RAAYAH SUKABUMI - Hidayat, Tatang; Arridho, Muhammad Hilmi; Istianah, Istianah (An-Nida : Jurnal Komunikasi Islam, 2024)
The purpose of this study is to analyze the qism amn da'wah strategy to improve the discipline of worship of STIBA Ar Raayah students. This research uses a qualitative approach and descriptive method. Based on the results of the study, the da'wah strategy is one of the excellent methods for the bearer of truth and also the institution that is used as a da'wah wasilah to achieve the desired target. Moreover, there is an opportunity to preach with the qism amn will facilitate da'wah so that it is easy to reach the destination. But most STIBA Ar Raayah students are already aware that the importance of worship, especially since they study religious knowledge daily. So qism amn is not too difficult to invite students to be more disciplined in worship.